The axial compressive experiment and analytical model for FRP-confined gangue aggregate concrete. (February 2022) - Wang, Jian; Xia, Junwu; Chang, Hongfei; Han, Youmin; Yu, Linli
Abstract: Coal gangue is the main industrial waste in the mining process, the best treatment is to completely replace the coarse aggregate and compound it into gangue aggregate concrete (GAC) to be used in the mining infrastructure construction. But the relatively inferior performance of GAC is the main factors limiting its application in structural components. Carbon fiber-reinforced polymer was employed as an external confinement to form a novel composite column (i.e. CFRP-confined GAC column) with optimized performance. To evaluate the mechanical behavior of the novel CFRP-confined GAC column, different inner core strength and outer CFRP jacket thickness were taken as the variables in the monotonic axial compression test. The results show that the confined GAC exhibited apparent volumetric compaction behavior and the compressive strength and ductility were greatly enhanced, but when the thickness of the CFRP jacket exceeds two layers, this improvement turned insignificant. In addition, the confinement stiffness had a more obvious effect on the dilation properties of the confined GAC compared with confined normal aggregate concrete (NAC). Furthermore, in order to provide support for the subsequent design and analysis of the confined GAC, the modified models for the dilation properties, ultimate strength and the corresponding ultimate strain of CFRP-confined GAC column were established combined with the confinement stiffness ratio and strain ratio. In addition, the incremental process of obtaining the stress–strain relationship curve was also redefined.